The Art of Baitul MaalwaTamwil (BMT) as Islamic Microfinance Institution in Eradicating Poverty and the Framework to Analyse its Performance - Atiqi Chollisni (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2013)
The nature of microfinance is to provide financial services andassist the poor people to become economically independent.Different with conventional microfinance that offers thefinancing scheme based on interest (read;riba), Islamicmicrofinance offers the financing scheme based on shariahprinciples to enhance the development of microentrepreneurs.The paper aims to present the art of baitulmaalwatamwil (BMT)as Islamic microfinance institution in eradicating poverty andpropose a conceptual model on the performance of BMT byanalyzing its efficiency. In the last twenty years, the growth ofBMTs increase significantly and have contributed positively tothe development of socio economic in Indonesia. Recently, it isestimated 4,000 BMTs operated and have enhanced thousandpoor people life. The paper believes that Islamic ethics offers byBMTs have attracted and accepted by society. The paper alsoidentifies the appropriate methods to evaluate efficiency ofBMTs, such evaluation of Islamic microfinance institution tofunction effectively to achieve socio economic objective inorder to increase its performance. The findings are not onlyrelevant and applicable to Indonesia but also to other muslimcountries and would be useful for further empirical research inthis area.